Analisis Kesalahan Penggunaan Bahasa Indonesia dalam Penulisan Karangan Teks Slogan Siswa Kelas VIII di UPTD SMP Negeri 1 Gunungsitoli - Tri Rahmat Laoli (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The ability of students’ writing skills in class VIII is related to the use of spelling (letters). Capitalization) and word selection (meaning) in writing slogan text compositions for students are still lacking. This study aims to analyze errors in the use of Indonesian in writing slogan text compositions for class VIII students at UPTD SMP Negeri 1 Gunungsitoli. This study is a qualitative descriptive study. The data for this study are student worksheets in writing slogan text compositions. The data sources in this study were class VIII-F students at UPTD SMP Negeri 1 Gunungsitoli and one of the Indonesian language teachers. The research instruments were tables of Indonesian language errors in writing slogan text compositions and interviews. Data collection techniques were observation, interviews and written tests. The data analysis technique in this study was reduction. Data, data presentation, and drawing conclusions. Based on the results of the research that has been conducted, the errors in Indonesian language in writing slogan text compositions found 161 errors in the use of Indonesian language in writing slogan text compositions of class VIII-F students including: (1) the use of spelling (capital letters) as many as 31 errors, starting from errors in the placement of capital letters (capital) and placement or use of lower case letters in writing student slogan texts, (2) word selection as many as 72 errors